Les « réseaux de nez », une négociation sur le proche - Élisabeth Rémy (Projets de Paysage)
With the « nose networks» coordinated by the Air Normand association, we tackle the issue of the cohabitation of a priori antinomic entities on a same space. Voluntary citizens were willing to become « noses» trained to record, over a long period of time, olfactions according to a specific protocol. At the same time, some manufacturers committed themselves into an « odour» approach by training « internal noses». The issue of smell nuisances seems to be limitless and questions the notions of space or territory. From then on, what does proximity mean when one mentions that kind of nuisances ? How are these knowledge integrated into the common research of solutions ? The test of the place of living gives makes enquiries about the effective « point of view» (in the double critical and geographical acceptance) through which the residents really take and pose the problems. At last, one could not underestimate the political impact of such a device insofar as it contributes to the building of the agreement between the different stakeholders.